Robot-assisted laparoscopic surgery versus conventional laparoscopic surgery in randomized controlled trials: A systematic review and meta-analysis. - Hyunsuk Frank Roh; Seung Hyuk Nam; Jung Mogg Kim (PLoS ONE, 2018)
Importance This review provides a comprehensive comparison of treatment outcomes between robot-assisted laparoscopic surgery (RLS) and conventional laparoscopic surgery (CLS) based on randomly-controlled trials (RCTs). Objectives We employed RCTs to provide a systematic review that will enable the relevant community to weigh the effectiveness and efficacy of surgical robotics in controversial fields on surgical procedures both overall and on each individual surgical procedure. Evidence review A search was conducted for RCTs in PubMed, EMBASE, and Cochrane databases from 1981 to 2016. Among a total of 1,517 articles, 27 clinical reports with a mean sample size of 65 patients per report (32.7 patients who underwent RLS and 32.5 who underwent CLS), met the inclusion criteria. Findings CLS shows significant advantages in total operative time, net operative time, total complication rate, and operative cost (p < 0.05 in all cases), whereas the estimated blood loss was less in RLS (p < 0.05). As subgroup analyses, conversion rate on colectomy and length of hospital stay on hysterectomy statistically favors RLS (p < 0.05). Conclusions Despite higher operative cost, RLS does not result in statistically better treatment outcomes, with the exception of lower estimated blood loss. Operative time and total complication rate are significantly more favorable with CLS.